Investigating the Vehicle Routing Problem with Simultaneous Pickup and Delivery in Multi-Product Distribution: An Optimization Approach - Irvanu Rahman; Komarudin Komarudin; Frans Samuel (International Journal of Supply Chain Management, 2020)
This study addresses a method to solve the Vehicle Routing Problem with Simultaneous Pickup and Delivery (VRPSPD), which carries multi-products in multiple compartments within a single-vehicle. The unique characteristics of the study is on the route determination of the vehicle from the depot to customers because not only does it consider the vehicle’s capacity but also the compartment capacity of each product as a limitation We calculate the set of instances using two customer grouping methods namely smallest maximum load (SML) and largest maximum load (LML). The solution obtained by the cheapest insertion method can be improved by the Tabu Search algorithm. Finally, the computational result is reported from the test instance.